Percepciones sobre la evaluación de algunos profesionales y usuarios de los programas nutricionales en Medellín, Colombia (2015)
ABSTRACT: With the emergence of social programs, there was also a need to evaluate the resources invested in them. The most widely used methods for evaluating programs and policies are the quantitative, but in recent years the emergence of evaluations that combine methods was seen, which generates the need to revalue the actors. Objective: To know some of perceptions of assessment the actors involved in social programs assume. Materials and methods: A qualitative study based on semi-structured interviews and focal group was made. Seven participants of the programs, 4 community leaders and 13 nutrition and dietetics professionals were interviewed in Medellin. Professionals in a corporation which operates with the social programs participated in the focal group. Results: The following categories related to the evaluation of social programs was identified from the analyzed information in the interviews: the conception of evaluation, the object of the evaluation, subjects and actors in the evaluation and assessment strategies. Conclusions: In general, the actors do not identify the importance of the process of evaluation of social programs. Besides, they have a welfare vision of such interventions, contrary to a universal approach and human rights.